Best management practices among the tobacco cultivators in Bachok district, Kelantan - Hasanah Mohamad (2011)
The National Kenaf and Tobacco Board is one of the authorities that is responsible to ensure all the tobacco planters have legal license, not planted over the limit and provide practices that recommended for them. In Bachok, Kelantan the total number of tobacco planters in year 2010/2011 is 1372 out of 3007 (total number of tobacco planters in Kelantan) included 141 male and 46 female were studied. We used 28 questionnaires included demography; the rest questionnaire related how they implement the practices during land preparation, chemical application, weeding, irrigation and healths. Result of crosstab correlations analysis indicated most of them not interested to implement the Best Management Practices that recommended by the authority and they prefer to do their own ways. They also not fully adopted the change of technology especially in watering system such as using sprinkler. The poor family background, low in education and also live in rural areas was the reasons they unable to change their mindset and difficult to practices the BMPs since they are familiar with their own ways. On the other hand, they are been exposed in hazardous chemicals such as pesticides, fertilizers, herbicides and fungicides. Based on the health facts 2010 from the Bachok Outpatient Clinic, M.A Zalami B. Hj. Md Yaakob said that farmers that been exposed directly or indirectly with hazardous situation have high probability of poisoning and toxic effect, acute upper respiratory tract infections, remainder of disease of the respiratory system, asthma and skin problems such as dermatitis and eczema, psoriasis, urticaria and impetigo. However, most of the tobacco planters assume they are healthy enough even though they are not wearing Proper Protections Equipment like mask, gloves, boots and others. Mostly, the female tobacco planters tend to be honest in giving information compared to the male tobacco planters.